2020
DOI: 10.1051/fopen/2020006
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19: SARS-CoV-2 susceptibility in healthcare workers – cluster study at a German Teaching Hospital

Abstract: Purpose: The local health department (in German: Gesundheitsamt) ordered a shutdown of a teaching hospital due to the severe acute respiratory syndrome coronavirus (SARS-CoV-2) outbreak – one index patient and five infected healthcare workers – and put it under quarantine. For the first time, all patients plus all employees of one German hospital (healthcare providers, physicians, and nurses) were tested to detect silent or asymptomatic carriers. Methods: A serial polymerase chain reaction (PCR) test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…There are, however, also reports of high seroprevalence among HCWs in Germany. A recently published study reported a 10- to 20-fold increased risk for HCWs to acquire a SARS-CoV-2 infection at work [ 26 ]. However, this study was done in a large academic teaching hospital with a COVID-19-positive patient load of up to 34.5%, which is not comparable to the number of COVID-19 patients seen in the medical center investigated in this study (36 cases between 1 January and 7 April 2020).…”
Section: Discussionmentioning
confidence: 99%
“…There are, however, also reports of high seroprevalence among HCWs in Germany. A recently published study reported a 10- to 20-fold increased risk for HCWs to acquire a SARS-CoV-2 infection at work [ 26 ]. However, this study was done in a large academic teaching hospital with a COVID-19-positive patient load of up to 34.5%, which is not comparable to the number of COVID-19 patients seen in the medical center investigated in this study (36 cases between 1 January and 7 April 2020).…”
Section: Discussionmentioning
confidence: 99%
“…A detailed epidemiological/phylogenetic study from South Africa showed that one SARS-CoV-2-infected person led to clusters in different hospital wards, leading to 39 infected patients and 80 infected staff members (35). Likewise, a recent report from a German teaching hospital demonstrated that only one index COVID-19 patient led to five infected staff members, subsequently resulting in more than 30% of infected hospitalized patients, emphasizing the need for a widespread SARS-CoV-2 testing and rapid isolation of positive cases (14). Thus, it is imperative to provide a safe hospital environment for patients and employees.…”
Section: Discussionmentioning
confidence: 99%
“…Infectiousness in the early stage of the disease and transmissions in the presymptomatic state or from persons with an asymptomatic course of the disease is likely high (10)(11)(12). This has been shown to cause clusters in vulnerable population, such as residents of nursing homes, as well as hospitalized patients (13,14). Likewise, caretakers and healthcare workers (HCWs) are at increased risk of SARS-CoV-2 infection (15,16).…”
Section: Introductionmentioning
confidence: 99%
“…In a hospital that was shut down due to a COVID-19 outbreak (COVID-19 positive rate of 35% among the 132 remaining patients) the risk of COVID infection for HCWs was 10-to 20-fold higher (and especially high in nurses) compared to the general population. 51 COVID-19 risk was investigated in 28,792 Danish HCWs by screening for IgM and IgG serum antibodies against SARS-CoV-2 and comparing to blood donors. 52 Seroprevalence was highest in HCWs on COVID-19 wards (P < 0.0001) followed by front-line HCWs (P < 0.0001).…”
Section: Surgeon and Health Care Worker Safetymentioning
confidence: 99%